(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This piece of research endeavour to analyse the poetical structure of one of the most recognizable Umayyad poets. He was the poet of the sensitive imagination that is dominated by mind. He used to handle, and as well critically probe, each of his poems singly. This had manifested his poetry as well-structured, fully-fledged talendedness, accurate expressions and fluent pouring of thoughts. He stood as one of the most apparent three poets of their period: Jareer and al-Farazdaq. He had highlighted the literary heritage and superby handled it. This piece of research attempts to concentrate on the most obvious characteristics of the human self as observed by al-Akhtal al-Kabeer through penetrating his literary style, the most distinguishable psychological features, and studying these features quite considerably. Toward this temptation, the research tends to examine these most recognizable features in the anthology of the great poet al-Akhtal al-Kabeer where he constitutes a unique experience in the field of the literary and poetical creativity: he surpasses his peers and contemporary poets, and gains the admiration of the authoritative circles. All this continues in an attempt to recognize the the most promoted features of this self, and the deep influence that the Arabic literary production witnesses.